Echinococcus granulosus genotypes in Iran: a systematic review. Issue 2 (2nd April 2018) - Khademvatan, S.; Majidiani, H.; Foroutan, M.; Hazrati Tappeh, K.; Aryamand, S.; Khalkhali, H.R.
Abstract: Cystic echinococcosis (CE) caused by Echinococcus granulosus sensu lato (s.l.) is a significant zoonosis, especially in developing countries of the Middle East, with many studies focusing on CE genotypes in Iran. We performed a systematic review to determine the exact status of E. granulosus genotypes in the country. We explored English (Pubmed, Scopus, ISI Web of Science and Science Direct) and Persian (Magiran, Iran Medex and Scientific Information Database) databases along with Google Scholar. Our review included 73 studies published prior to the end of 2015. In total, 2952 animal (intermediate and definitive) hosts were examined, and the prevalent genotypes comprised G1 (92.75%) and G6 (4.53%) in sheep, cattle, camels, goats and buffaloes; G3 (2.43%) in five herbivore hosts and dogs; G7 (0.2%) in sheep and goats; and G2 (0.06%) in dogs. G1 was mostly dominant in West Azerbaijan, whereas G3 and G6 were identified most frequently in the provinces of Isfahan and Fars, respectively. Regarding human CE infection, 340 cases were reported from Iran, with the identified genotypes G1 (n = 320), G6 (n = 13) and G3 (n = 7). Most CE-infected humans originated from Isfahan province (168 cases), whereas the lowest number of infected persons was noted in Kerman province (two cases). The information obtained from this systematic review is central to better understanding the biological and epidemiological characteristics of E. granulosus s.l. genotypes in Iran, leading to more comprehensive control strategies.